On the geometry of Poincaré's problem for one-dimensional projective foliations - SOARES,MARCIO G. (2001)
We consider the question of relating extrinsic geometric characters of a smooth irreducible complex projective variety, which is invariant by a one-dimensional holomorphic foliation on a complex projective space, to geometric objects associated to the foliation.